Simbiosis entre empresa y sociedad: el caso del Banco Galicia y el Museo de Ciencias Naturales de La Plata (2012)
Corporate social responsibility (CSR) is a topic that has come to the forefront in the field of administration. Generally, it is analyzed in shades of white or black, from a virtually utopian or critical perspective. The purpose of this article is to demonstrate that CSR should be studied from a third perspective in which today’s companies face the new challenge of sustainability. CSR can be a very good strategy for achieving sustainability, thus resulting in a mutually beneficial and delicate symbiosis between business and society. To account for this, we opted to carry out case studies and complement them with interviews and documentary analysis.